2000
DOI: 10.1002/(sici)1521-3773(20000403)39:7<1267::aid-anie1267>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

A Supramolecular Enzyme Mimic That Catalyzes the 15,15′ Double Bond Scission of ,-Carotene

Abstract: Two Ru‐porphyrin‐linked β‐cyclodextrin units form the supramolecular system, which as an enzyme mimic for β,β‐carotene 15,15′‐dioxgenase binds two substrates of the enzyme with Ka>106 M−1 and selectively catalyzes the cleavage of the central carotinoid bond in the presence of tert‐butylhydroperoxide (see picture). Mechanistic aspects of this unusual cleavage of E‐configured, conjugated double bonds are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(48 citation statements)
references
References 8 publications
(13 reference statements)
1
46
0
1
Order By: Relevance
“…The ruthenium catalyst afforded cleavage at C15-C15', C12'-C11', and at C10'-C9' in an overall yield of 30 %. However, the selective cleavage of C15-C15' was observed when one of the cyclohexene end groups of β,β-carotene was replaced by an ortho-dimethylphenyl group [211] . Other catalytic investigations targeted the electrochemical oxidation of sugars for applications as fuel in fuel cells.…”
Section: Catalysismentioning
confidence: 99%
“…The ruthenium catalyst afforded cleavage at C15-C15', C12'-C11', and at C10'-C9' in an overall yield of 30 %. However, the selective cleavage of C15-C15' was observed when one of the cyclohexene end groups of β,β-carotene was replaced by an ortho-dimethylphenyl group [211] . Other catalytic investigations targeted the electrochemical oxidation of sugars for applications as fuel in fuel cells.…”
Section: Catalysismentioning
confidence: 99%
“…However, it was recently shown that carotenoid hydroxylation is catalyzed by CYP 450 in bacteria [69] and in plants [70,71]. A well-developed and elegant porphyrin model of a catalytic system has been used to mimic the central cleavage of carotenoids [72]. The reaction was about 40 % regioselective for the oxidative cleavage of β-carotene on its central (15,15') carbon-carbon double bond.…”
Section: Carail and C Caris-veyratmentioning
confidence: 99%
“…The filtrate was concentrated on a rotary evaporator and the residue distilled at 0. 15 (8) 6.04 6.12 6.12 HÀC(8') 6.04 6.12 6.12 HÀC(10) 6.08 6.6 6.6 HÀC(10') 6.08 6.10 6.6 HÀC(11) 6.62 6.31 6.31 HÀC (11') 6.62 6.62 6.31 HÀC (12) 6.29 6.04 6.05 HÀC(12') 6.29 6.29 6.05 HÀC (13) 6.34 6.85 6.85 HÀC(13') 6.34 6.34 6.85 HÀC (14) 6.30 6.31 6.31 HÀC(14') 6.30 6.31 6.31 HÀC (15) 6.30 6.37 6.37 HÀC(15') 6.30 6.30 6.37 (10) 6.10 6.53 6.53 HÀC(10') 6.10 6.11 6.53 HÀC (11) 6.61 6.35 6.37 HÀC (11') 6.61 6.61 6.37 HÀC (12) 6.31 6.09 6.10 HÀC(12') 6.31 6.31 6.10 HÀC(13) 6.32 6.78 6.79 HÀC(13') 6.32 6.32 6.79 HÀC (14) 6.32 6.32 6.37 HÀC(14') 6.32 6.32 6.37 HÀC (15) 6.32 6.32 6.38 HÀC(15') 6.32 6.32 6.38 was chromatographed on an Alox II N column (hexane/benzene 4 : 1) to give, after evaporation, 569 mg of an orange oil. It was rechromatographed on an Alox II N column (hexane/benzene 5 : 1) to yield, after evaporation, a yellow oil (377 mg, 44%) of a mixture of three isomers of 15 1 ).…”
Section: Experimental Partmentioning
confidence: 99%
“…Parallel to our efforts to purify the native protein [7] and to determine the reaction mechanism [10], we developed a synthetic supramolecular enzyme model that catalyzes carotenoid cleavage [11] [12], and we also investigated the substrate specificity of b,b-carotene 15,15'-monooxygenase from chicken intestinal mucosa using enriched enzyme fractions. We wish to report here the synthesis of several potential substrates and incubation experiments with 14 substrate analogues.…”
Section: Introduction ± Bb-carotenementioning
confidence: 99%